On the Meaning of Aspects in Russian - Галнайтите, Э. (Kalbotyra, 1977)
In present-day Russian linguistics there exist different interpretations of the semantics of aspects. The meaning of the perfective aspect is understood either as the limitation of an action (V. Vinogradov a. o.) or as its completion (J. Maslov a. o.).The present paper points out that in some cases V. Vinogradov’s concept is modified by substituting the term “inner limitation” for “limitation”. The former term is notionally narrower than the latter. Besides, the term “inner limitation” is associated with the lexico-grammatical category of terminativeness/non-terminativeness.The author of the present paper considers the theory of V. Vinogradov to be better motivated and more convincing. Attention is drawn to the fact that the meaning of aspect, i. e. the limitation of an action, is in its very nature grammatical and not nominative as some linguists tend to think.